Molecular characterization of the garlic virus B genome and evidence of allexivirus recombination - Celli, Marcos Giovani; Perotto, Maria Cecilia; Luciani, Cecilia Elizabeth; Pozzi, Elizabeth Alicia; Conci, Vilma Cecilia (Springer, 2018)
Molecular characterization is important for differentiating allexiviruses species, since detection by serological methods may be uncertain. Eight different species have been reported as infecting garlic: Garlic virus A, B, C, D, E, X (GarV-A, B, C, D, E, X), Shallot virus X (ShVX) and Garlic mite-borne filamentous virus (GarMbFV), and the complete genome is known for six of these. This work reports for the first time the complete sequence of GarV-B and makes a phylogenetic and recombination analysis between the different allexivirus species. Total RNA was obtained of a GarV-B positive garlic plant by ISEM-D using anti-GarV-B antiserum and this was sent for mass sequencing. Deep sequencing revealed the first complete GarV-B genome, consisting of 8327 nucleotides (nt). The genome contained six open reading frames (ORFs) with the typical genome organization which encodes putative proteins of 168 kDa (ORF1), 27 kDa (ORF2), 12 kDa (ORF3), 39 kDa (ORF4), 27 kDa (ORF5) and 14 kDa (ORF6). The comparison of the gene coding for the coat protein of the virus showed a greater identity of nt with other isolates of GarV-B (88.4 to 99.7%) and of GarV-X (75.4 to 78.3%) published in GenBank. The GarV-B replicase gene has not been previously reported in GenBank, so the sequence was compared with GarV-A, -C, −D, −E, −X and ShVX. The highest nt identity values were detected with isolates of GarV-X (73.5 to 74.1%) and GarV-C (71.9 to 72.8%). These results suggest that GarV-X and GarV-B may be different strains of the same virus. A genetic recombination analysis was also performed between the complete sequences of allexiviruses published and obtained in this work and it was detected that the species GarV-D and GarV-E may have arisen from the recombination of the N-terminal portion of GarV-B with the C-terminal portion of GarV-A.